2019
DOI: 10.1021/acs.jpclett.9b02750
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermal Properties in Formamidinium and Cs-Mixed Lead Halides

Abstract: Formamidinium [FA, HC­(NH2)2 +] lead iodide and its cation mixture have attracted interest as potentials in applications for efficient solar cells superior to well-known methylammonium lead iodide. We investigated the crystal structure and thermodynamic properties of high-quality single crystals of FA1–x Cs x PbI3 for x = 0 and 0.1 through X-ray diffraction and heat capacity measurements. Both α-FA0.9Cs0.1PbI3 as well as α-FAPbI3 crystallize in a cubic Pm3̅m structure with orientationally disordered FA molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 52 publications
5
48
0
Order By: Relevance
“…With decreasing temperature from T = 300 K, the PL spectra narrow and start to redshift from T = 150 K, with additional anomalous broadening ( Supporting Information section S4, Figure S8a), likely connected to the low-energy rattling of the MA cation. 54 We observe no anomalous broadening of the PL for the x = 0.2 and x = 0.5 compositions ( Figure S8b,c ), in agreement with a reduction in MA cation motion as a result of preferential alignment and a smaller unit cell volume compared to x = 0. In contrast to x = 0, the x = 0.5 composition shows a sharp jump in the spectral peak position around T = 180 K ( Figure 6 c), which can be attributed to emission from Br-rich regions following photo-induced halide segregation.…”
Section: Resultssupporting
confidence: 74%
“…With decreasing temperature from T = 300 K, the PL spectra narrow and start to redshift from T = 150 K, with additional anomalous broadening ( Supporting Information section S4, Figure S8a), likely connected to the low-energy rattling of the MA cation. 54 We observe no anomalous broadening of the PL for the x = 0.2 and x = 0.5 compositions ( Figure S8b,c ), in agreement with a reduction in MA cation motion as a result of preferential alignment and a smaller unit cell volume compared to x = 0. In contrast to x = 0, the x = 0.5 composition shows a sharp jump in the spectral peak position around T = 180 K ( Figure 6 c), which can be attributed to emission from Br-rich regions following photo-induced halide segregation.…”
Section: Resultssupporting
confidence: 74%
“…Reproduced with permission. [ 26 ] Copyright 2019, American Chemical Society. e) Scheme on the phase and polymorphism behavior of FAPbI 3 .…”
Section: The Structure and Phase Behavior Of Fapbi3 Perovskitementioning
confidence: 99%
“…[ 24,25 ] Figure 1d showed the comparison between the temperature dependence of heat capacity for FAPbI 3 and FA 1– x Cs x PbI 3 with different phases. [ 26 ] It can be observed that there are additional two first‐order transition between β‐ and γ‐phases in FAPbI 3 . The disappearance of multiple transitions in FA 1– x Cs x PbI 3 indicates that the cation doping can affect the structural transitions of FA‐based perovskite.…”
Section: The Structure and Phase Behavior Of Fapbi3 Perovskitementioning
confidence: 99%
“…(25-28) However, depositing high quality CsxFA1-xPbI3 (x>0.5) with both high PV performance and no phase segregation is still challenging because of the large lattice mismatch and different phase transition temperature between FAPbI3 and CsPbI3 perovskites. (29,30) Herein we demonstrate intrinsically stable Br free phase pure CsxFA1-xPbI3 (x=0.5-0.9) perovskites with tunable wide band gap, which did not exhibit any phase segregation under thermal or light stress. Specifically, the Br free Cs0.7FA0.3PbI3 perovskite with 1.65 eV band gap exhibits intrinsically thermal and photo stability in comparison with the typical I-Br mixed halide perovskites of MAPb(I0.8Br0.2)3 and Cs0.25FA0.75Pb(I0.8Br0.2)3.…”
Section: Introductionmentioning
confidence: 83%